Cloning and genetic diversity analysis of a new P5CS gene from common bean (Phaseolus vulgaris L.) - Chen, J.; Zhang, X.; Jing, R; Blair, Matthew W.; Mao, X; Wang, S. (Springer, 2010)
?1-pyrroline-5-carboxylate synthetase (P5CS) is the rate-limiting enzyme involved in the biosynthesis of proline in plants. By the 3? rapid amplification of cDNA ends (3?-RACE) approach, a 2,246-bp cDNA sequence was obtained from common bean (Phaseolus vulgaris L.), denominated PvP5CS2 differing from another P5CS gene that we cloned previously from common bean (PvP5CS). The predicted amino acid sequence of PvP5CS2 has an overall 93.2% identity GmP5CS (Glycine max L. P5CS). However, PvP5CS2 shows only 83.7% identity in amino acid sequence to PvP5CS, suggesting PvP5CS2 represents a homolog of the soybean P5CS gene. Abundant indel (insertion and deletion events) and SNP (single nucleotide polymorphisms) were found in the cloned PvP5CS2 genome sequence when comparing 24 cultivated and 3 wild common bean accessions and these in turn reflected aspects of common bean evolution. Sequence alignment showed that genotypes from the same gene pool had similar nucleotide variation, while genotypes from different gene pools had distinctly different nucleotide variation for PvP5CS2. Furthermore, diversity along the gene sequence was not evenly distributed, being low in the glutamic-g-semialdehyde dehydrogenase catalyzing region, moderate in the Glu-5-kinase catalyzing region and high in the intervening region. Neutrality tests showed that PvP5CS2 was a conserved gene undergoing negative selection. A new marker (Pv97) was developed for genetic mapping of PvP5CS2 based on an indel between DOR364 and G19833 sequences and the gene was located between markers Bng126 and BMd045 on chromosome b01. The relationship of PvP5CS2 and a previously cloned pyrroline-5-carboxylate synthetase gene as well as the implications of this work on selecting for drought tolerance in common bean are discussed.